Star Wars maker lab - Heinecke, Liz Lee; Horton, Cole (DK Publishing, 2018)
Offers young Star Wars fans projects and experiments inspired by the Star Wars universe, including instructions on making Jabba slime, Kyber crystals, and an Ewok catapult.